Developing a model software to determine the effect of High Voltage Transmission Lines (HVTL) on the residential land value by using AHP method - Marabaoğlu, Seda Nur; Uzun, Bayram (International Journal of Strategic Property Management, 2024)
Due to High Voltage Transmission Lines (HVTL), easement expropriation is made and an easement price (compensation) is paid to the property owner. Since there is not a standard method, this price is calculated inappropriately and inaccurately. Therefore, either the property owner or the government suffers material damage. The main objective of this study is to determine the impact of HVTL factors on property value using the Analytical Hierarchy Process (AHP) method. Additionally, within the scope of the study, the aim is to develop a software model that automatically detects impairment rate and easement prices. In the study, a total of 79 individuals from 21 different countries participated in the national and international survey. The weights of the factors were determined using the AHP. A model software was created by integrating the weight values and the interface software of the model was created. The model software was tested with sixty expert reports prepared by different experts collected from ten different provinces. The rate of error in the expert reports was found to be at least 0.38% and at most 84.98%. With this software, an appraisal standard that will largely eliminate the existing injustices in the determination of the easement price will be provided. In addition, the inconsistencies between the expert reports of similar parcels and easements will be reduced, and easement prices will be paid fairly.